Liberal vs Liberating Empowerment: A Latin American Feminist Perspective on Conceptualising Women's Empowerment - Sardenberg, Cecília Maria Bacellar (2008)
Paper prepared for presentation to the Conference: Reclaiming Feminism – Gender and Neo-Liberalism, Institute of Development Studies (IDS), Brighton, UK, 9-10 July 2007. A previous version of this paper was presented at the Pathways of Women’s Empowerment Research Programme Consortium Inception Workshop, Luxor, Egypt, September 2006.